The malaria care cascade and factors associated with receiving a malaria test in children under 5 years of age and pregnant women with fever: a cross-sectional household survey from three regions in Guinea and three districts in Sierra Leone in 2022 - Alexandre Delamou; Heide Weishaar; Charbel El Bcheraoui; Francisco Pozo-Martin; Abdul Karim Mbawah; Hanna-Tina Fischer; Gerrit Burger; Klara Röbl; Lukas Feddern; Brogan Geurts; Habibata Baldé; Ibrahima Kaba; et al. (BMJ Global Health)
Introduction Malaria remains a significant global health issue, particularly among children under 5 years of age and pregnant women. In Guinea and Sierra Leone, malaria care in these vulnerable groups remains suboptimal and may have deteriorated due to the COVID-19 pandemic. Thus, evidence on the state of the malaria care cascade is urgently needed to guide public health interventions after the COVID-19 pandemic.Methods We conducted a cross-sectional household survey to evaluate the state of the malaria care cascade—in terms of care-seeking, diagnosis, treatment and outcomes—and explore factors associated with receiving malaria testing during an episode of fever among children under 5 years of age and pregnant women during the COVID-19 pandemic between May and August 2022. Steps of the care cascade were assessed against WHO recommendations, and factors associated with receiving a malaria test were explored by multivariable regression.Results We surveyed caregivers of 1377 children under 5 years of age and 254 pregnant women with an episode of fever in three regions and three districts in Guinea and Sierra Leone, respectively. Reported malaria testing rates varied from 42% to 96% in children and 62% to 91% in pregnant women by region/district. Trust in the healthcare system, not avoiding health facilities, receiving informative messages about malaria and pregnant women attending antenatal care (ANC) services were factors associated with receiving a malaria test. Between 54% and 81% of children and 24% to 69% of pregnant women with malaria received treatment within 2 days of fever-onset by region/district, while delays were reported at all steps of the care cascade. Hospitalisation due to the malaria episode was reported by 6.5% and 4.3% of children, as well as 9.5% and 12% of pregnant women in Guinea and Sierra Leone, respectively.Conclusion Our study reveals maintained reported use of malaria care services during the COVID-19 pandemic and heterogeneous potential for improvement along all steps of the malaria care cascade in Guinea and Sierra Leone. Interventions promoting trust in the healthcare system, informative malaria messages and ANC coverage among pregnant women may improve malaria care in both countries.